FAKTOR-FAKTOR PENENTU PENYEBARAN HIV(+)/AIDS DI INDONESIA Tahun 2008 - Vetty Priscilla (Faculty of Medicine, Universitas Andalas, 2008)
AbstrakIndonesia merupakan negara yang paling cepat terjadinya penularan HIV di kawasan Asia Tenggara. Diperkirakan pada tahun 2010 penderita HIV(+)/AIDS akan meningkat menjadi 400.000 orang dengan perkiraan kematian 100.000 orang. Penyebaran utama terjadi di kalangan penyalahgunaan narkoba dengan jarum suntik dan pekerja seks komersil. Di samping itu, penyebaran HIV dipengaruhi oleh faktor-faktor tertentu seperti faktor sosial ekonomi/kemiskinan, jenis kelamin, perilaku dan gaya hidup, sosial budaya, biologi dan pelayanan kesehatan.Kata Kunci ;HIV/AIDS, faktor penentu, IndonesiaAbstractThe epidemic of HIV/AIDS is spreading at a significantly higher rate in Indonesia compared to other South-East Asia. Highly cases of HIV/AIDS in Indonesia indicated that by the year 2010 the number of AIDS cases will have increased to 400.000, with 100.000 deaths. The majority of HIV/AIDS patients are found among high-risk populations, especially among the Intravenous Drug Users (IDUs) and sex workers. In these two groups the infection is spreading very rapidly. Some determinants of health of HIV/AIDS become vulnerable in Indonesia such social-economic/poverty, gender, lifestyle and behavior, socio-culture, biological and health care.Keywords; HIV/AIDS, determinants, IndonesiaTINJAUAN PUSTAKA